G207(P) Hypernatremia in early neonatal life- can it be physiological?. (12th March 2018) - Ahmad, I; Ahmed, A; Dar, SA; Bhat, JI; Ali, SW; Charoo, BA; Ahmad, QI; Bhat, MA
Abstract : Aims: To monitor serum sodium levels (in mEq/l) in healthy term/near-term infants in early neonatal period. To identify risk factors for hypernatremic dehydration and possible early interventions. Methods: Only healthy term/near-term inborn babies were included. They were examined on days four, seven and ten of life. Blood samples were collected on days four and ten of life, serum was separated and stored at −20°C for subsequent analysis for sodium. Serum sodium was compared with weight loss and different risk factors were analysed for association with hypernatremia. Results: 184 healthy term/near-term neonates were included. Mean serum sodium was 149±6.0 (135–172). Sodium levels were normal (135–145) in 47 (25.5%) neonates; hypernatremia of varying severity was detected in 137 (74.5%). 62 (33.7%) neonates had serum sodium levels between 146 and 150, 62 (33.7%) between 151 and 159, and 13 (7%) had serum sodium ≥160. By day 10 of life sodium levels had normalised in all except one, who was hospitalised on day 5 of life with hypernatremic dehydration. His day 4 serum sodium was subsequently found to be 172. Association of different risk factors with hypernatremia is in the table 1. Signs of dehydration were discernible in only nine patients and all of them had hypernatremia, however, most of the babies didn't have obvious dehydration signs. Conclusion: Mild to moderate hypernatremic dehydration is quite common in early neonatal period and adequate breastfeeding is an effective and safe intervention.